Influence of light, food and predator presence on the activity pattern of the European spiny lobster Palinurus elephas: An investigation using tri-axial accelerometers. (June 2020) - Zenone, Arturo; Ciancio, Javier E.; Badalamenti, Fabio; Buffa, Gaspare; D'Anna, Giovanni; Pipitone, Carlo; Giacalone, Maximiliano V.
Highlights: Accelerometers proved to be a promising tool to monitor the activity and behavior of lobsters. The analysis pointed at the variance of roll body angle as the best proxy for lobster activity. The presence of a predator caused a strong reduction of lobster activity. In the presence of food lobsters reduced their activity in hours previous to sunrise. Abstract: The knowledge of the activity pattern of marine organisms represents a crucial aspect in the studies on their ecology. In this paper, we used for the first time data from tri-axial accelerometers to provide an accurate description of the activity pattern of the European spiny lobster, Palinurus elephas . Sixteen lobsters (8 males, 8 females) were tagged with tri-axial accelerometers in order to monitor their activity in a mesocosm during four replicate trials. In each trial the lobsters were submitted to three treatments of the duration of one day each: exploration, presence of food and presence of a predator. The variance of roll body angle (VariRoll) was chosen among a number of available variables as a proxy of lobster activity during each treatment. The lobsters were more active during the night and in low-light hours than during the day. Moreover, they were i) more active without food or predator, ii) less active in the presence of a predator, iii) with an intermediate activity level (i.e. values of VariRoll) in the presence of food. Besides contributing to the knowledge of P. elephas ecology, the results of this study provide a new analytical method to describe activity patterns in slow-moving animals.